Effect of pine bark extract and its phenolic compounds on selected pathogenic and probiotic bacterial strains - Sánchez-Moya, Teresa; López-Nicolás, Rubén; Peso-Echarri, Patricia; González-Bermúdez, Carlos A.; Frontela-Saseta, Carmen (Frontiers in Nutrition, 2024)
Inflammatory bowel disease (IBD) comprises a heterogeneous group of chronic diseases as ulcerative colitis (UC) and Crohn's disease (CD). IBD is the result of a dysregulation of intestinal homeostasis with a host´s loss of tolerance towards normal enteric microflora. Plant-based extracts as phenolic compounds can play a role by modulating the intestinal inflammation response. The in vitro antimicrobial activity of French maritime pine bark extract (PBE) and its phenolic constituents has been investigated in this study. Furthermore, the ability of PBE and phenolic compounds (caffeic acid, chlorogenic acid, ferulic acid, gallic acid and taxifolin) to modulate the microbiota has been assessed. Phenolic compounds and PBE showed a great inhibitory effect on the pathogens growth at the highest concentration assessed (1.25 mg/mL). The growth of E. sakazakii and E. faecalis were affected by the effect of caffeic acid and ferulic acid. Taxifolin showed a very strong activity against Listeria sp. (with a reduction ~98%). Gallic acid revealed antibacterial effect on S. aureus at different concentrations.The inhibitory effect of PBE was highly significant on the growth of E. coli O157:H7. PBE, caffeic acid and chlorogenic acid seem to provide the greatest beneficial effect on the probiotic bacteria.However, the highest concentrations of taxifolin may have impaired the growth of beneficial microbiota. Present findings could be of interest for considering PBE and/or its phenolic constituents as protectors against gastrointestinal disturbances which lead to ulcerative colitis and Crohn's disease.